Chlamydia psittaci: a suspected cause of reproductive loss in three Victorian horses. Issue 11 (23rd August 2020) - Akter, R; Stent, AW; Sansom, FM; Gilkerson, JR; Burden, C; Devlin, JM; Legione, AR; El‐Hage, CM
Abstract : Chlamydia psittaci was detected by PCR in the lung and equine foetal membranes of two aborted equine foetuses and one weak foal from two different studs in Victoria, Australia. The abortions occurred in September 2019 in two mares sharing a paddock northeast of Melbourne. The weak foal was born in October 2019 in a similar geographical region and died soon after birth despite receiving veterinary care. The detection of C. psittaci DNA in the lung and equine foetal membranes of the aborted or weak foals and the absence of any other factors that are commonly associated with abortion or neonatal death suggest that this pathogen may be the cause of the reproductive loss. The detection of C. psittaci in these cases is consistent with the recent detection of C. psittaci in association with equine abortion in New South Wales. These cases in Victoria show that C. psittaci, and the zoonotic risk it poses, should be considered in association with equine reproductive loss in other areas of Australia.